Protective effect of Tanshinone IIA on LPS-induced canine endometritis - FU, KAIQIANG; FENG, CHAO; SUN, GUANZHENG; GAO, FENG; WANG, ZEZHI; SUN, YUNING; LI, HUATAO; FENG, YANNI; HUAN, YANJUN; TIAN, WENRU; CAO, RONGFENG (The Indian Journal of Animal Sciences, 2021)
Canine endometritis is a common disease in dogs. This work intends to establish the model of lipopolysaccharide (LPS) -induced canine endometritis, and investigate the effect of Tanshinone IIA (Tan IIA) on canine endometritis. At first, we tested the rectal temperature and the production of IL-1β and TNF-α at 6 h, 12 h, 18 h and 24 h after LPS administration. Then 9 beagles were divided into 3 groups on average, all beagles received intraperitoneal injection of saline solution (group 1 and 2) or Tan IIA (group 3) at 6 h before and after LPS challenge. Beagles of group 2 and 3 were performed uterine infusion of LPS, and beagles of group 1 were performed uterine infusion of saline solution. The rectal temperature was measured 6 h, 12 h, 18 h, 24 h post-LPS challenge, all uterus were collected after 24 h post-LPS challenge. The results showed that canine endometritis can be established by LPS at the concentration of 0.5 mg/kg of body weight after 24 h performance. The rectal temperature, the production of IL-1β and TNF-α increased significantly when the model was established. The results showed that rectal temperature, production of IL-1β and TNF-α and the expression of IL-6 were significantly reduced after treatment with Tan IIA compared with the group of LPS challenge only. However, the expression of IL-10 increased after Tan IIA treatment. Considering the positive anti-inflammation effect on the LPS-induced canine endometritis, Tan IIA may be used as a therapeutic agent to treat the clinical canine endometritis.